Winter´s biomechanics and motor control of human movement - Thomas, S. J.; Zeni, J. A.; Winter, D. A. (Wiley, 2023)
An In-Depth Resource for Understanding the Foundational Concepts and Clinical Applications in the Field of Biomechanics